Durability assessment of laser treated aluminium bonded joints. (September 2019) - Musiari, F.; Moroni, F.; Favi, C.; Pirondi, A.
Abstract: Structural adhesives are widely used in industrial applications dealing with the problem of assembly and bonding. Despite the several advantages brought by this technique, one of the main issue is represented by the need of the surface to be mechanically and/or chemically treated with the aim to make it suitable for the adhesive deposition. Previous works demonstrate how the surface treatment by laser ablation seems to enhance the joint strength with respect to the untreated material. In particular, the effect of pulsed Yb-laser ablated aluminium surfaces over the mode I energy release rate of Double Cantilever Beam (DCB) specimens was investigated and a significant growth of the fracture toughness compared with the untreated and the grit blasted joints was observed. In this work, an investigation concerning the durability of the mechanical properties of aluminium joints treated with several representative parameters configurations was conduced. These setting configurations were used in an experimental campaign with the aim of verifying their suitability varying the type of the test (fatigue tests) and the environmental conditioning of the specimens (quasi-static tests after ageing cycles). Concerning the fatigue behavior, the ranking of the laser parameters configuration according to the increase of toughness with respect the degreased and the grit blasted samples seemed quite consistent with the results obtained in the quasi-static test campaign. When an accelerated ageing cycle in control of temperature and relative humidity was applied, a general lowering of toughness affected every tested specimen. This effect was however more marked in the grit blasted sample than in the laser treated ones. Therefore, a relative improvement of the mechanical performance when using some laser ablation configurations instead of the grit blasting, under the same conditions, when the adhesively bonded joints were aimed to undergo some critical environmental exposure, was recorded.